An Evaluation of In-Hospital Stroke in Irish Acute Hospitals - Chapman, Lucy Ellen (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2024)
Introduction Between 1 and 17% of strokes occur in-hospital in patients hospitalised for another reason. In-hospital strokes are associated with worse outcomes and poor performance on quality-of-care measures of acute stroke care. Methods A retrospective multi-centre cohort study comparing in-hospital and community-onset strokes was conducted using stroke data collected for the purposes of the Irish National Audit of Stroke from the 1st of January 2020 to the 31st of December 2021. Results Of 10,781 stroke cases, 618 occurred in patients in-hospital stroke equating to 5.7% of strokes. In-hospital stroke patients were older (Median age 76 years [IQR 67 to 84 years] versus 74 years [IQR 64 to 82 years] of community-onset stroke). Patients with an in-hospital stroke were more likely to have an ischaemic stroke (90.0% versus 85.4%; p=0.002, pre-stroke disability (modified Rankin score of 3 to 5 30.6% versus 14.3%; p<.001), atrial fibrillation (40.6% versus 29.8%; p<.001) than community-onset stroke patients. The median [IQR] length-of-stay was longer for in-hospital stroke (14 [6-30] versus 8 [4-16] days) and admission to the stroke unit was less frequent (44.2% versus 70.2% of community-onset strokes; adjusted odds ratio 0.46 95% CI 0.38-0.56; p<.001). Longer median [IQR] times to medical assessment (20 [5-84] versus 12 [0-100] minutes; p<.001) and thrombolysis (90 [63-135] versus 54 [37-80] minutes; p<.001) were observed for patients with an in-hospital onset compared with community-onset stroke. Thrombolysis rates were lower amongst ischaemic stroke patients with in-hospital onset (8.7%) versus community-onset stroke (9.9%; p=0.36). One in four (27.2%) in-hospital onset stroke cases die in-hospital compared with one in ten (10.4%) community-onset strokes (adjusted odds ratio 2.98 [2.37-3.75]; p<.001). Favourable functional ability was less likely at discharge for in-hospital onset stroke cases (28.9% versus 52.3% of community-onset strokes; adjusted odds ratio 0.38 [0.30-0.48]; p<.001). Conclusions The Irish cohort of in-hospital stroke patients reflect a distinct stroke subgroup. Longer delays to medical assessment and thrombolysis, poorer functional outcomes and increased in-hospital mortality were observed highlighting opportunities to improve care for patients with in-hospital stroke onset.
APPROVED
Keywords: community-onset stroke; outcomes; quality-of-care measures; in-hospital stroke